Research Profile of Student Independence in Elementary Schools - Indrawati, Mamik; Mariana, Neni; Muhimmah, Hitta Alfi (Raudhah Publisher, 2025)
This research aims to determine the profile of students' learning independence through various research study results from both national and international journals. The samples taken used 15 types of journals and articles related to the independence profile of students in elementary schools. Using literature study techniques, the results obtained show that various media, methods, approaches, use of information and communication technology, teacher readiness in planning, implementing and evaluating learning have an effect on the independence of students in elementary schools. Apart from that, support and motivation from other adults, especially teachers and parents, have a very important role in forming students' independence. This is an effort by teachers or educational units to prepare a generation that is strong, independent and responsible as the foundation for children to face global challenges in the future.